Anti Fraud dan Whistleblowing Intention: Peran Intensitas Moral dan Pengambilan Keputusan Etis - Riantika, Reny Lia (AFRE (Accounting and Financial Review), 2021)
The purpose of this study was to determine the role of moral intensity and ethical decision making in influencing fraud and whistleblowing. Reluctance to report known violations can be overcome through the implementation of an effective, transparent and responsible whistleblowing system. With this system, it is hoped that it will increase the level of employee participation in reporting violations. This study uses a purposive sampling method with the considerations that the samples taken are employees of private higher education educators in Yogyakarta who have permanent status and have work experience of more than 5 years. The data analysis technique uses Path Analysis. Based on the results of the analysis, it shows that there is an effect of Moral Intensity on Whistleblowing Intention. Ethical decision making has an effect on Whistleblowing Intention. Moral Intensity has an effect on Fraud; and ethical decision making has an effect on Fraud and there is an effect of Whistleblowing Intention on Fraud. Tujuan penelitian ini adalah untuk mengetahui peran intensitas moral dan pengambilan keputusan etis dalam mempengaruhi fraud dan whistleblowing. Keengganan untuk melaporkan pelanggaran yang diketahui dapat diatasi melalui penerapan whistleblowing system yang efektif, transparan dan bertanggungjawab. Dengan adanya sistem ini di-harapkan dapat meningkatkan tingkat partisipasi karyawan dalam melaporkan pelanggaran. Penelitian ini menggunakan metode purposive sampling dengan pertimbangan-pertimbangan bahwa sampel yang diambil adalah karyawan tenaga pendidik Perguruan Tinggi Swasta di Yogyakarta yang berstatus tetap dan memiliki pengalaman kerja diatas 5 tahun. Teknik analisis data menggunakan Analisis Jalur (Path Analysis). Berdasarkan hasil analisis menunjukkan terdapat pengaruh Intensitas Moral terhadap Whistleblowing Intention. Pengambilan keputusan etis berpenagruh terhadap Whistleblowing Intention. Intensitas Moral berpengaruh terhadap Fraud; danÂ  pengambilan keputusan etis berpengaruh terhadap Fraud serta terdapat pengaruh Whistleblowing Intention terhadap Fraud DOI: https://doi.org/10.26905/afr.v4i1.5957